Fables Reading Skills of Ants and Pigeons for Class III SDN Cibedug 01 - Siti Asiah (Mitra Palupi, 2023)
Background: Reading is part of the four language skills. Reading plays an important role in forming an intelligent, critical and creative generation. Basically, the ability and skill to read is a mandatory requirement. Therefore, the ability to read must be cultivated from an early age. To improve the reading ability of grade III elementary school students, fairy tales can be used Purpose: The purpose of this study was to determine the level of students' ability to read the Ants and Pigeons fable. Design and methods: The research method is a qualitative descriptive research. The subjects of this research were grade III students of SD Negeri CIBEDUG 01. Data analysis techniques using the Miles and Huberman models included data collection, data reduction, data presentation, and drawing conclusions or examination. Results: The results of this study on the Ability to Read Fables at SD Negeri CIBEDUG 01 can be categorized into Very Good (12%), Good (61%), Enough (24%) and Needs Guidance (3%) categories. Based on the findings, motivational factors within students affect the enthusiasm for learning to read fairy tales in elementary schools. In addition, reading fairy tales is considered difficult to understand by students.